Application of Lean Manufacturing in Tofu Production to Reduce Waste - Muttaqin, Muhammad Faishal Jundana; Sholeha, Riska Wirdatus; Yanuarso, Hersa Dwi; Aulia, Lina; Wahyudi, Rizqi; Iqbal, Muhammad (Jurnal Multidisiplin Indonesia, 2024)
DRK Tahu is a micro business producing various types of tofu, including white ones. This business is located in Gading Rejo District, Pringsewu. There are three types of waste found in the tofu-cutting process: transportation, delay, and storage. Transportation activities and delays cause a waste of time when completing the cutting process. The time required for the entire tofu cutting activity in one process is 832.65 seconds because the cutting work method still uses a wooden frame and a knife. The percentage of the value-added ratio before the improvement was made was 0.33%. This research aims to reduce waste and help optimize the cutting process to be more efficient and effective. The principle of lean manufacturing is used as a method for overcoming problems. The lean manufacturing tool used in this study is Process Activity Mapping (PAM). PAM is used to identify value-added, necessary non-value-added, and non-value-added activities so that the production process becomes lean. The analysis of the factors causing waste was carried out using a fishbone diagram. The proposed improvement for the cause of the problem is through designing a tofu-cutting tool. The implementation results are time savings of 153.87 seconds and an increased value-added ratio of 0.11%.